Innovative ADDIE-Based PhET Worksheet for Physics Learning in Limited-Laboratory Contexts - Purwandari Purwandari; Farida Huriawati; Erawan Kurniadi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This research is motivated by the main gap in physics learning, namely the lack of experimental activities due to limited laboratory facilities and the lack of systematic integration between PhET simulations and inquiry-based teaching tools. Although various studies have shown the effectiveness of virtual laboratories in improving conceptual understanding, there are still few studies that have developed structured digital LKPDs using the ADDIE model and empirically assess its impact on students' scientific attitudes. This research uses a Research and Development (R&D) design based on the ADDIE model which includes the analysis, design, development, and implementation stages. The effectiveness test was carried out using a one-group pretest–posttest design on 35 students in grade XI. Expert validation data was analyzed using a percentage of eligibility, while the improvement in students' scientific attitude was analyzed with descriptive statistics and N-Gain calculations to measure the relative improvement before and after treatment. The results showed that LKPD obtained the feasibility of 80.4% of material experts and 82.5% of media experts, both in the feasible category. The implementation of PhET-based LKPD resulted in an increase in scientific attitudes with an N-Gain value of 0.43 (medium category), indicating moderate effectiveness in facilitating virtual inquiry activities. Theoretically, this study contributes in the form of an integration model between digital LKPD, PhET simulation, and inquiry frameworks that can be replicated in the context of laboratory limitations. Practically, this product can be an innovative alternative teaching tool for physics teachers to support inquiry-based learning in limited facilities.